AN UNUSUAL FOREIGN BODY BRONCHUS (OPEN SAFETY PIN): An Unusual Foreign Body Bronchus - Ali, Muhammad; Aslam, Sohail; Majeed, Farhan Ahmed; Ashfaq, Muhammad (Pakistan Armed Forces Medical Journal, 2008)
.